SPATIAL ANALYSIS OF COASTLINE CHANGE BY REMOTE SENSING IN THE NORTH COAST OF KARAWANG REGENCY - Pasaribu, Roberto; H, Firman Agus; Soeprijadi, Liliek (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2019)
The existence of the coast in the northern part of Karawang Regency is very worrying. Seawater that was far up to tens of meters from the side of the road, is now on the lip of the road, even some parts of the road are cut off due to abrasion of seawater. Some villages were affected by abrasion erosion. One of the effects of damage due to abrasion and sedimentation is the occurrence of shoreline changes. This change in coastline will affect people's lives and spatial planning for the development of the area. For this reason, this study aims to determine the extent and rate of shoreline changes that occurred on the coast of Karawang Regency in the periods of 1989, 1995, 2001, 2005, 2009, 2016, and 2018. The shoreline data was obtained from the extraction of Landsat 3 MSS, Landsat 5 TM, Landsat 7 ETM +, and Landsat 8 OLI-TIRS after the NDWI process was previously carried out. While the rate of change is calculated at 6 sample point locations scattered along the northern coast of Karawang Regency. The results showed that the largest area damaged by abrasion occurred in Sedari Village covering an area of 166.802 hectares, and the area formed by the largest sedimentation occurred in Muara Cilamaya Village at 276,318 hectares. Meanwhile, the fastest rate of shoreline change due to abrasion occurred in Sukajaya Village at 10 meters /year, while the slowest in Sedari Village at 3.77 meters / year. The fastest sedimentation process in Muara Cimalaya Village is 4.5 meters / year, while the late one in Tanjung Pakis Village is 3.09 meters / year.